GPER mediates the up-regulation of acid synthase (fasn) intuced by 17B-estradiol in cancer cell and in cancer-associated fibroblasts (CAFs) - Santolla, Maria Francesca; Maggiolini, Marcello; Sisci, Diego (My University, 2012)
Activation of lipid metabolism is an early event in carcinogenesis and a central hallmark of many tumors. Fatty acid synthase (FASN) is a key lipogenic enzyme catalyzing the terminal steps in the de novo biogenesis of fatty acids. In cancer cells, FASN may act as a metabolic oncogene given that it confers growth and survival advantages to these cells, whereas its inhibition effectively and selectively kills tumor cells. Hormones like estrogens and growth factors contribute to the transcriptional regulation of FASN expression also through the activation of downstream signaling and a crosstalk among diverse transduction pathways. In this study, we demonstrate for the first time that 17β-estradiol (E2) and the selective GPER ligand G-1 regulate FASN expression and activity through the GPER-mediated signaling which involved the EGFR/ERK/c-fos/AP1 transduction pathway, as ascertained by using specific pharmacological inhibitors, performing gene-silencing experiments and ChiP assays in breast SkBr3, colorectal LoVo, hepatocarcinoma HepG2 cancer cells and breast cancerassociated fibroblasts (CAFs). In addition, the proliferative effects induced by E2 and G-1 in these cells involved FASN as the inhibitor of its activity, named cerulenin, abolished the growth response to both ligands. Our data suggest that GPER may be included among the transduction mediators involved by estrogens in regulating FASN expression and activity in cancer cells and CAFs that strongly contribute to cancer progression.
Dottorato di Ricerca in Biochimica Cellulare ed Attività dei Farmaci in Oncologia, XXV Ciclo
Keywords: Estrogens; Fatty acids